The Structure of Artistic Expanse in Marina Tsvetaeva’s Autobiographical Essay Mother and Music - Бетко, Ирина (Slavia Orientalis, 2020)
The article is devoted to study of the structure of the artistic expanse in Marina Tsvetaeva’s autobiographical essay Mother and Music. This structure is rich and complex; containing the following elements: concrete-geographical, spatial-physical, archetypal, emotional-psychological, sacred‑spiritual as well as others. Each of them, to one degree or another, reflects the peculiarities of the writer’s worldview, her creative manner, as well as her subjective attitude to the objective phenomena of surrounding reality. In the holistic context of this essay, the author contrasts two grandiose Universes – the mother’s world with her music and the daughter’s world with her poetry. The relativity and variability of the relevant spatial, psychological and other parameters emphasize the absoluteness of those eternal values of existence, on which the masterly organized system of Tsvetaeva’s prose is based.
Keywords: structure; artistic expanse; Marina Tsvetaeva; the autobiographical essay 'Mother and Music'